Posts, Likes, Shares, and DMs: A Qualitative Exploration of How Social Media Is Related to Sexual Agency in Young People. Issue 2 (1st February 2021) - Cooper, Spring; Schobert, Kelsey; Cheruvillil, Sonia; Porter, Andrew; Palmedo, P. Christopher
ABSTRACT: It is well documented that social interactions have a crucial impact on all aspects of personal development for adolescents, however few studies have documented how social interactions affect a young person's sense of sexual agency. The aim of the current qualitative study was to examine young people's perceptions of their own sexual agency in relation to their social media attitudes and behaviors. Participants (n = 31) were recruited from a nonprofit organization and asked to complete a one-hour in-depth interview and a demographic survey. Using an inductive method, involving constant comparison, we identified four overarching themes: (a) Participants utilize different social media platforms for distinct purposes and are cognizant of each audience; (b) Based on past experiences, participants have negotiated and created their own rules of engagement for online behavior; (c) Participants have different expectations about how others should act online versus how they act in relation to flirty or sexual messages; (d) Participants were concerned about the authenticity of online identities and are aware of vulnerability in online interactions. Our results highlight the need for sexual health researchers to observe social network etiquette closely through the lens of autonomy and agency.